Implementation of K-Means Algorithm in Determining Clustering of Lion Air Pilots: Implementasi Algoritma K-Means Dalam Menentukan Klasterisasi Pilot Lion Air - Ahmad Jurnaidi Wahidin (SYSTEMATICS, 2021)
Covid-19 was declared a pandemic by WHO on March 11, 2020, and President Joko Widodo through the Head of BNPB declared the COVID-19 outbreak a National Disaster. To limit people's mobility, the government issued a Regulation of the Minister of Transportation concerning Transportation Control in which operators of transportation facilities are obliged to supervise and ensure the implementation of physical distancing. One of the sectors affected by the COVID-19 pandemic is transportation, the government is looking for a solution to minimize this impact by providing incentive stimulus to airlines and also reducing the Air Passenger Service tariff by 20% to reducing aviation fuel prices by 10%, but the government's efforts have not succeeded. . The implementation of PPKM together with the Circular Letter of the Ministry of Transportation Number SE 88 of 2021 has reduced the interest of airplane passengers. This situation made the Lion Air airline reduce 8000 employees to pilots. However, pilots are applied to fly alternately by dividing into several groups. By using the k-means algorithm which is one of the clustering methods in data mining, the division of groups can be done by partitioning the data into several clusters. so that data with the same characteristics will be grouped into one cluster. The results of processing 730 lion air pilot data with three clusters resulted in 431 cluster 1 data, 200 data cluster 2 and 99 data cluster 3, from the three clusters dominated by the age of 20-35 years with a working period of 6-11 years but with an average different average flying hours and working hours.